Relevance of incorporating intercultural perspective in the care and health promotion - López Borbón, Dilana (2014)
The purpose of this essay is to reflect about the relevance on the intercultural perspective, taking into consideration the globalization process and social interactions in pluricultural contexts. The emphasis is incorporated this perspective in nursing care and health promotion. Firstly, health is considered a right which is possible to promote the dignity, equality and social justice. Moreover, intercultural perspective promotes the coherence between health strategies and social needs, through to extend the vision of health interventions. Following, it is relevant to incorporate this perspective in the professional education and daily practices. To conclude, it is necessary to integrate this perspective in the care provision and health promotion in order to have a positive impact in the society as well to guarantee the humans health right